A Native Long Horned Beetle Promotes the Saproxylic Diversity in Exotic Plantations of Monterrey Pine - Vergara-Egert, P; Fierro-Tapia, C (Elsevier B.V., 2019)
Native saproxylic (deadwood dependent) beetle species living in exotic forest plantations may provide environmental services for forestry companies, but their sensitivity to forest management makes them difficult to conserve. Here, we used Structural Equation Models (SEM) to assess the role of the endemic beetle Acanthinodera cumingii in native forest and exotic pine plantations as an ecosystem engineer that improves the quality of deadwood for saproxylic beetles. Deadwood quality in native forest and pine plantations was accounted for by A. cumingii density and deadwood decay stage. In native forest, diversity of predators and fungivores responded positively to deadwood quality, while in the pine plantations the diversity of all functional groups, with exception of detritivores, was positively affected by deadwood quality. In addition, all saproxylic functional groups were less diverse in stumps than in logs. These findings suggest that A. cumingii larvae contribute to make more diverse the assemblages of saproxylic beetles in deadwood. We suggest that sustainable management of pine plantations based on the role of A. cumingii as an ecosystem engineer and biodiversity indicator must necessarily consider forest practices intended to mimic the native forest conditions that regulate the deadwood decay dynamics. © 2018 Elsevier Ltd